Concussion in collegiate athletics: A link to academic achievement. (November 2020) - Walter, Alexa E; Kaschak, Christian; Sebastianelli, Wayne; Arnett, Peter; Slobounov, Semyon M
Context: After concussion, many different symptoms can occur and persist that can affect daily functioning. Many of these symptoms could have implications in an athlete's ability to return to academics. Unlike return to play, return to academics is less studied and less regulated. There is little research examining the effects of concussion on grade point average (GPA) and results have been inconsistent. Objective: To examine the effects of concussion on college GPA. Design: Retrospective observational study Setting: University laboratory Participants: Division I athletes after their first concussion (n = 26) and Division I athletes without a history of concussion (n = 30). Main Outcome Measures: GPA and demographic information was obtained for the semester before injury, the semester of injury, and the semester after injury. Results: Statistical analysis using generalized linear mixed model analysis revealed a significant interaction ( p < 0.05) of group (concussion vs. control) by time, with the concussed group having a significant decrease in GPA from semester before injury to semester of injury, and a significant main effect for sex ( p < 0.05 ) with females having higher GPAs than males. Conclusions: Since the cognitive demands of academics can potentially exacerbate symptomology of concussion, the identification of students at risk for difficulties is critical.